GŁOS CESARZA HADRIANA W SPRAWIE S.C. SILANIANUM - Amielańczyk, Krzysztof (Zeszyty Prawnicze, 2017)
Hadrian's Resolutions in s.c. Silanianum Summary S.c. Silanianum (10 B.C.) introduced a common responsibility of slaves who did not try to rescue the master although they stayed in the same house or nearby, even at the risk of their own life. Tortures and death penalty awaited them. By means of his rescripta, Hadrian attempted to make the strict law more precise so that the liability should rest only on the slaves that were really guilty of unfulfilling their duties towards the master. If no other possibilities, the duty to help could be carried out at least by calling for help. The Emperor demanded that an effective defence which really aimed at saving the master should be undertaken. The investigation and capital punishment were provided only for those slaves who stayed near the place of the murder, close enough to be able to see the threat and undertake an attempt to prevent it. Hadrian’s solutions reflect the maxim In maleficiis voluntas spectatur non exitus. It was not the master’s death that should lead to the slave’s liability but his guilt of being passive.